1999
DOI: 10.1007/s002469900437
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Cardiac Troponin I in the Acute Stage of Kawasaki Disease

Abstract: The study was performed to investigate the level of serum cardiac troponin I (cTnI), a marker specific for myocardial damage, using a chemiluminescent immunoassay in the acute febrile stage of Kawasaki disease (KD). The study population consisted of 45 KD patients before intravenous gamma-globulin (IVGG) therapy and a control group of 20 patients without KD. Among KD patients the results from measurements of the level of cTnI were positive in 18 cases (40%) and the creatine kinase (CK)-MB was positive in 11 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 20 publications
(17 reference statements)
1
21
1
Order By: Relevance
“…81 Elevation of serum cardiac troponin I, a marker that is specific for myocardial damage, has been reported in acute Kawasaki disease, which is consistent with myocardial cell injury in the early phase of the disease. 82,83 Such elevation was not confirmed in another study. 84 Troponin assays do not play a role in the routine management of children with Kawasaki disease.…”
Section: Laboratory Findingsmentioning
confidence: 50%
“…81 Elevation of serum cardiac troponin I, a marker that is specific for myocardial damage, has been reported in acute Kawasaki disease, which is consistent with myocardial cell injury in the early phase of the disease. 82,83 Such elevation was not confirmed in another study. 84 Troponin assays do not play a role in the routine management of children with Kawasaki disease.…”
Section: Laboratory Findingsmentioning
confidence: 50%
“…The values returned to normal in 16 of 18 after treatment with intravenous immunoglobulin but remained elevated in 2 patients who continued to have clinical myocarditis and heart failure. 54,56 Another author compared 29 patients with KD with 11 controls and found that cTnI did not reliably exceed the predetermined threshold of 0.2 mcg/L in subjects with KD. The authors did not comment on the potential relevance or statistical significance of the fact that the 2 groups of patients with KD had mean cTnI values of 0.11 and 0.15 mg/L compared with controls who had mean values of 0.04 mg/L.…”
Section: Kawasaki Diseasementioning
confidence: 98%
“…Cardiac complications occur in up to 20% of affected individuals and include myocarditis, pericardial effusion, congestive heart failure, conduction system abnormalities, and structural damage to the coronary arteries. 54,55 Prompt administration of intravenous immunoglobulin can significantly reduce the incidence of cardiac complications, so timely diagnosis is important. With increasing appreciation of atypical KD, scenarios like the one outlined in the opening of this review confront clinicians regularly.…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…During the acute phase of KD, a variety of inflammatory factors induce dysfunctions of endothelia of the coronary artery, such as spasm, ischemia of the coronary artery, that contributes to subsequent cardiac-muscle damage [23] . Because of the over-activated inflammatory response and the apparent endothelial damage, damage to the cardiac muscle in the CAL group was more severe than in the NCAL group.…”
Section: Ctnimentioning
confidence: 99%